Trends, challenges and opportunities in the in situ conservation of cereal landraces in Scottish islands - Martin, Peter; Shoemark, Olivia; Scholten, Maria; Wishart, John; Drucker, Adam G.; Maxted, Nigel (European Cooperative Programme for Plant Genetic Resources (ECPGR), 2023)
Landraces are traditional crop varieties that often have special adaptations to the farming environment in which they have evolved and are therefore a valuable source of useful traits for plant breeders. In most agriculturally advanced countries, landraces of the main crops have generally been superseded by modern varieties. An exception to this in the United Kingdom is the cultivation on the Scottish archipelagos of Orkney, Shetland and the Outer Hebrides of three cereal landraces: bere, a 6-row barley (Hordeum vulgare), small oat (Avena strigosa) and Hebridean rye (Secale cereale). Our study focused on trends in their cultivation and use over the past 20 years. In the Outer Hebrides, a mixture of all three has continued to be grown on more than 200ha for feed because of its tolerance of nutrient-deﬁcient sandy soils. Future cultivation is threatened, however, by damage from geese and deer, especially to ﬁelds used for seed production. In Orkney and Shetland, only bere and small oat are grown, and always as sole crops. The area of bere has increased in Orkney, from about 10ha in 2004 to almost 75ha in 2020 and has been driven by two supply chains producing bere for milling and malting. However, small oat in Orkney, and both small oat and, especially bere, in Shetland have been grown by very few farmers since 2018 and are at serious risk of being lost from cultivation. We discuss these results in the context of measures to support greater on-farm cultivation of these landraces.